Influencia de portainjertos en la calidad y productividad del pomelo Paraná (Citrus sp.) - Lezcano, Cecilia Carolina; Torres, Cesar Gaston; Beltran, Victor Manuel; Gochez, Alberto Martin; Soliz, Jorge Andres; Benitez, Rolando Jose; Monzon, Héctor Andrés; Vallejos, Victor Pablo; Vallejos, Aníbal; Hermosis, Fabián; Canteros, Blanca Isabel (Asociación Argentina de Horticultura (ASAHo), 2024)
Poster